Dietary Klebsormidium sp. Supplementation Improves Growth Performance, Antioxidant and Anti-Inflammatory Status, Metabolism, and Mid-Intestine Morphology of Litopenaeus Vannamei - Fang, HaoHang; Zhuang, ZhenXiao; Huang, LuoDong; Zhao, Wei; Niu, Jin (Frontiers in Nutrition, 2022)
Filamentous microalga Klebsormidium sp. has huge potential to become a natural and healthy additive in aquatic feed since it contains various bioactive nutrients, such as linoleic acid (LA), carotenoids, and chlorophylls. Therefore, an eight-week feeding experiment was performed to evaluate the effects of dietary Klebsormidium sp. on the growth performance, antioxidant and anti-inflammatory status, metabolism, and mid-intestine morphology of Litopenaeus vannamei. Two isonitrogenous and isolipid diets supplemented with and without 5% Klebsormidium sp. were prepared. Results showed that L. vannamei fed with Klebsormidium sp. had better growth performance and feed utilization by optimizing mid-intestine morphology and improving the carbohydrate metabolism. In addition, Klebsormidium sp. also enhanced the antioxidant capacity of L. vannamei by downregulating antioxidant parameters (hepatopancreas T-SOD, hepatopancreas GSH-PX, hemolymph T-SOD, hemolymph MDA) and RNA expression levels of antioxidant genes (gsh-px and cat). Furthermore, the supplementations of dietary Klebsormidium sp. significantly improved hepatopancreas health by downregulating RNA expression levels of pro-inflammatory related genes (relish and rho). Therefore, a dose of 5% Klebsormidium sp. is recommended for the daily diet of L. vannamei to improve the growth performance, antioxidant and anti-inflammatory status, metabolism, and mid-intestine morphology of shrimp.